Crown Gall Induced by a Natural Isolate of Brucella (Ochrobactrum) pseudogrignonense Containing a Tumor-Inducing Plasmid - Marjolein J. G. Hooykaas; Paul J. J. Hooykaas (Microorganisms)
Crown gall disease in plants is caused by “Agrobacteria”, bacteria belonging to the Rhizobiaceae family, which carry a tumor-inducing (Ti) plasmid. Unexpectedly, we found evidence that a natural isolate from a rose crown gall, called NBC51/LBA8980, was a bacterium that did not belong to the Rhizobiaceae family. Whole-genome sequencing revealed that this bacterium contained three large DNA circles with rRNA and tRNA genes, representing one chromosome and two chromids, respectively, and two megaplasmids, including a Ti plasmid. Average nucleotide identity (ANIb, ANIm) and genome-to-genome distance (GGDC) values above the thresholds of 96% and 70%, respectively, showed that NBC51/LBA8980 belonged to the species Brucella (Ochrobactrum) pseudogrignonense. Its Ti plasmid was almost identical to certain succinamopine Ti plasmids previously identified in Agrobacterium strains, suggesting that this Ti plasmid may have been recently acquired by NBC51/LBA8980 in the tumor environment.